Anticonvulsive effect of atorvastatin on pentylenetetrazole‐induced seizures in mice: the role of nitric oxide pathway. (19th March 2012) - Moazzami, Kasra; Emamzadeh‐Fard, Sahra; Shabani, Mohammad
Abstract Atorvastatin has shown to possess neuroprotective, antiexcitotoxic, and antiepileptic effects besides its cholesterol‐lowering properties. Nitric oxide (NO) may be responsible for a group of these effects. In the present study, a model of clonic seizure induced by pentylenetetrazole (PTZ) in male NMRI mice was used to investigate the anticonvulsive effects of atorvastatin through NO‐dependent pathways. Atorvastatin (5 mg/kg) significantly increased the seizure threshold (P < 0.001). Moreover, L‐arginine (a precursor of NO) significantly (P < 0.01) potentiated the anticonvulsive effects of subeffective doses of atorvastatin (1 mg/kg). Finally, L‐NAME [L‐arginine methyl ester dihydrochloride], a nonspecific NO synthase inhibitor, completely abolished the anticonvulsive properties of atorvastatin. Our findings demonstrated the role of atorvastatin as an anticonvulsive agent and showed the effects to be mediated through NO‐related pathways.